The impact of influencer power on consumers’ higher education brand trust: France & Canada compared - Griset, Léna; Menvielle, Loïck; Dash, Rupanwita (Management international / International Management / Gestiòn Internacional, 2025)
This research examines the role of social media influencers (SMIs) in higher education brand strategy, focusing on how their characteristics influence attitudes in a multicultural context. The model explores the relationships between SMIs’ attributes—social attractiveness, attitude homophily, and interactivity—and perceived expertise, authenticity, and trustworthiness, as well as their impact on brand trust. Based on a study of 276 participants using structural equation modeling, the findings reveal that SMIs significantly influence brand trust, with trustworthiness being the strongest predictor. Interestingly, authenticity had less impact, while global identity behaviors led to more uniform perceptions across diverse groups.